Does excluding students from co-creation of rubrics affect their academic achievement in the associated authentic assessment task?. Issue 4 (1st October 2020) - Ghosh, Samrat; Bowles, Marcus; Abeysiriwardhane, Apsara
ABSTRACT: Rubrics are assessment tools without which students have no guidelines towards their achievement or to understand the teacher's feedback. Although, traditionally designed by educators, students have been engaged to co-construct rubrics with their teachers. The authors of this paper set out to investigate the difference in the academic achievement (measured using assessment scores) when students are excluded versus included in rubric design. This paper presents the first phase of investigation when the students were excluded from rubric design intended to be used for the authentic assessment of their competence in the use of leadership skills. The authentic assessment was implemented as a formative assessment in the form of two separate and distinct assessments. The students were provided feedback on their performance in the first task using the rubrics constructed by the educators. The assessment scores revealed a significant number of students used the feedback to improve their academic achievement. Future research will present findings from the second phase of investigation when the students will co-create the rubrics and its impact on their academic achievement will be studied.